Study of dipion bottomonium transitions and search for the Hb(1P) state - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We study inclusive dipion decays using a sample of 108×106Υ(3S) events recorded with the BABAR detector. We search for the decay mode Υ(3S)→π+π−hb(1P) and find no evidence for the bottomonium spin-singlet state hb(1P) in the invariant mass distribution recoiling against the π+π− system. Assuming the hb(1P) mass to be 9.900 GeV/c2, we measure the upper limit on the branching fraction B[Υ(3S)→π+π−hb(1P)]<1.2×10−4, at 90% confidence level. We also investigate the χbJ(2P)→π+π−χbJ(1P), Υ(3S)→π+π−Υ(2S), and Υ(2S)→π+π−Υ(1S) dipion transitions and present an improved measurement of the branching fraction of the Υ(3S)→π+π−Υ(2S) decay and of the Υ(3S)−Υ(2S) mass difference.
Im Titel ist "b" tiefgestellt
Gesehen am 15.08.2022